(untitled) (Journal of the College of Education for Women, 2019)
Education, who is dignified the community and transmit a stagnation to the movement and chaos intothe system of the advancement and nettlesome to the production, so it is the human resource development focusof the overall development, as that man in general and university student in particular is a tool and purpose ofdevelopment together, there is no development without human From this perspective the researcher felt therewas a need to conduct a study to know the psychological stability among the students of the university and thedetection level of ambition, the following specific question? What is the relationship between the psychologicalstability level with the ambition among the students of the university?The importance of the current research through the role of university students in community-building andprogress forward, therefore, must maintain their mental health would like to be more ambitious in order toachieve the goals of the university and the community.ResearchObjectives:The objective of this research is to identify the psychological stability and level of ambition of theuniversity students and to identify statistically significant differences in the psychological stability and level ofambition according to the gender variable, as well as to identify the correlation between emotional stability andthe level of ambition.The research sampleIt is consisted of 200 students from the University of Baghdad and in the academic year (2010-2011), whilethe search tools have been preparing a measure of psychological stability by the researcher, and the adoption ofa measure the level of ambition .The researcher used a number of statistical methods to analyze data from:1 - test educational Administration2 - Pearson correlation coefficientThe results of the researchshowed the enjoyment of the research sample psychological stability and level of ambition, and the presenceof statistically significant differences in psychological stability depending on the gender variable in favor ofmales. And there is no difference in the level of ambition according to the gender variable, and the resultsshowed the presence of significant correlation between emotional stability and the level of ambition appearedabove search a number of conclusions and recommendations and proposals.